Treatment of ‘Baigent’ apple fruit with nitric oxide in controlled atmosphere storage reduces decay and physiological disorders - Coser W.* (2023)
© 2022The study was carried out to evaluate the effects of nitric oxide (NO) treatment at different doses and times during controlled atmosphere (CA) storage on quality of ‘Baigent’ apples. The evaluated treatments were: control; 10 µL L−1 of NO applied only at the beginning of CA storage; 1, 2 or 5 µL L−1 of NO applied every 30 d of CA storage; and 5 µL L−1 of NO applied at the beginning and at the end of CA storage. Fruit were stored for 7.5 months in 1.2 kPa O₂ + 2.0 kPa CO₂, 1.5 ± 0.2 °C, and relative humidity of 94 ± 2%. NO treatments, except 10 µL L−1 NO applied only at the beginning of CA storage, reduced ethylene production. At removal from CA storage, 5 µL L−1 NO, applied every 30 d of CA storage or at the beginning and at the end of CA storage, reduced respiratory rates. Control fruit and fruit treated with 2 µL L−1 NO every 30 d of CA storage had higher soluble solids content, and control fruit and fruit treated with NO at 1 or 2 µL L−1 every 30 d of CA storage had higher titratable acidity. NO treatments, regardless of the dose and application time during CA storage, delayed skin yellowing and reduced hydrogen peroxide content and the incidence of pulp mealiness. The application of 5 µL L−1 of NO at the beginning and at the end of CA storage maintained a higher total phenolic compound content and reduced the incidence of flesh browning. Treatment with 5 µL L−1 NO at the beginning and at the end of CA storage provided better quality maintenance of ‘Baigent’ apples.